Competitive Strategies in Student Recruitment Among Indonesian Universities: The Role of Digital Marketing, Social Media, and Institutional Branding - Andika, Aditya (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
The increasing competition among Indonesian higher education institutions, particularly in major cities on Java Island, has prompted universities to pay greater attention to strategies related to student recruitment. This study presents a literature-based review of marketing and management approaches reported in previous studies focusing on universities in Jakarta, Bandung, Surabaya, Yogyakarta, and Semarang. The review specifically examines discussions related to digital marketing, social media utilization, institutional branding, and reputation management within the context of higher education management. Based on the synthesis of the literature, this paper develops a conceptual framework that brings together elements of digital marketing effectiveness, social media marketing activities, brand equity development, and reputation management. The reviewed studies generally indicate that social media platforms, particularly Instagram, are frequently discussed as channels that may influence prospective students’ awareness and perceptions of universities. In addition, digital marketing practices such as content tailored to Generation Z, search engine advertising, and interactive social media activities are commonly reported as part of student recruitment efforts. This study contributes to the education management literature by summarizing existing research on university marketing in Indonesia and offering directions for future empirical investigation.